Navigating Uncertainties Towards Sustainable Feed Production for Indian Poultry and Cattle Farmers - Dharmapada Nath, Amiya (Digital Repository of Theses - SSBM Geneva, 2025)
Introduction: India‘s poultry and dairy farmers often operate under uncertain and challenging conditions. Unpredictable rainfall, limited irrigation facilities, and poor infrastructure make it difficult for farmers to manage livestock effectively. These challenges reduce productivity and income, especially for those who were in rural and semi-urban areas who heavily agricultural dependent and livestock for their livelihoods. Background: Over the years, various government initiatives have aimed to improve livestock productivity. However, farmers still face major obstacles, such as soil degradation, inadequate veterinary services, and poor access to affordable, sustainable feed. Moreover, market linkages remain weak, further limiting farmers‘ ability to scale up operations or ensure consistent income. Aim: This study aims to assess the impact of government interventions in addressing key challenges in poultry and dairy farming, with a focus on sustainable feed production and livestock services. Research Gap: While previous studies highlight productivity and technological advancements, they often overlook how government policies influence the overall livestock ecosystem. There is a lack of integrated analysis that connects policy impacts to feed availability, breeding programs, and veterinary services in rural India. This research work study seeks to bridge that gap by providing a comprehensive policy-oriented perspective. Research Methodology: Using a simple random sampling method, various data were collected from 400 farmers across rural and semi-urban regions between 2022 and 2023. A structured questionnaire covering six thematic areas was used. Data analysis included regression and Chi- Square tests. Results: Findings indicate that technology adoption, improved feed supply, and supportive policies significantly boost productivity and income (R² = 0.297–0.552, p < 0.001; χ² = 174.987–783.669, p < 0.001). However, inconsistencies in policy implementation persist. Originality: This study uniquely integrates policy analysis with technological and economic dimensions of livestock farming. Implications: The findings provides actionable insights for policymakers and stakeholders for improved infrastructure, training, and resource distribution to enhance sustainability in India‘s livestock sector. Keywords: Sustainable livestock farming, Poultry and dairy feed production, Government policies, Veterinary services, Technology adoption, Farmer challenges, Rural agricultural development